The Conflict with Lobstering, and Why Whales Are Critical to Ocean Health and the Gulf of Maine - Stephenson, Toby (Maine Policy Review, 2023)
Whales play a vital and under-appreciated role in maintaining the health of the entire Gulf of Maine ecosystem, and mitigating threats to whales will have benefits that reach all corners of the food web, from plankton to baitfish to lobster and far beyond. In this commentary, the author examine the conflict between Maine’s lobster industry and whales and discuss reasons why Maine people should be concerned about and try to protect whales and the overall health of the Gulf of Maine ecosystem.
Keywords: right whales; lobster fishery; whale entanglement